Digital Narratives and Cultural Exchanges in Sino-Philippine Friendship: A Corpus and Communication Analysis Based on Chinese Social Media - Guo, Aowei (Pacific International Journal, 2024)
This study delves into the digital narratives and cultural exchanges that frame Sino-Philippine friendship, primarily through data analyzed from the Chinese social media platforms Xiaohongshu and Weibo. In the current globalized context, the relationship between China and the Philippines transcends traditional diplomacy, prominently featuring in public opinion and media impacts. This research identifies and analyzes the primary digital narratives surrounding Sino-Philippine friendship on these platforms and assesses how these narratives influence cultural perceptions and emotional attitudes among the populace of both nations. Through a comprehensive methodological approach combining corpus construction with communication analysis, the study reveals the narratives predominantly focus on economic cooperation, cultural exchange, and shared challenges such as pandemic responses. It highlights a prevalent positive sentiment in the digital discourse, which not only fosters cultural understanding but also enhances bilateral relations. The findings underscore the significant role of digital media in shaping international relationships in the digital era, providing insights into the maintenance of international friendships through new forms of media interaction.